Homelessness and severe mental illness in low- and middle-income countries: scoping review. Issue 4 (July 2019) - Smartt, Caroline; Prince, Martin; Frissa, Souci; Eaton, Julian; Fekadu, Abebaw; Hanlon, Charlotte
Abstract : Background: Despite being a global problem, little is known about the relationship between severe mental illness (SMI) and homelessness in low- and middle-income countries (LMICs). Homeless people with SMI are an especially vulnerable population and face myriad health and social problems. In LMICs, low rates of treatment for mental illness, as well as differing family support systems and cultural responses to mental illness, may affect the causes and consequences of homelessness in people with SMI. Aims: To conduct a systematic, scoping review addressing the question: what is known about the co-occurrence of homelessness and SMI among adults living in LMICs? Method: We conducted an electronic search, a manual search and we consulted with experts. Two reviewers screened titles and abstracts, assessed publications for eligibility and appraised study quality. Results: Of the 49 included publications, quality was generally low: they were characterised by poor or unclear methodology and reporting of results. A total of 7 publications presented the prevalence of SMI among homeless people; 12 presented the prevalence of homelessness among those with SMI. Only five publications described interventions for this population; only one included an evaluation component. Conclusions: Evidence shows an association between homelessness and SMI in LMICs, however there is little information on the complex relationship and direction of causality between the phenomena. Existing programmes should undergo rigorous evaluation to identify key aspects required for individuals to achieve sustainable recovery. Respect for human rights should be paramount when conducting research with this population. Declaration of interest: None.